The mediating effect of e-health literacy on social support and behavioral decision-making on glycemic management in pregnant women with gestational diabetes: a cross-sectional study - Peng Yumei; Ke Huiying; Shen Liqin; Zhao Xiaoshan; Zhao Meijing; Xie Yaping; Zhao Huifen (Frontiers Media S.A., 2024)
BackgroundSocial support and e-health literacy are closely related to individual health behaviors, while behavior is premised on decision-making. Few studies have identified the relationships among social support, e-health literacy, and behavioral decision-making, and the nature of these relationships among pregnant women with gestational diabetes remains unclear. Therefore, this study aimed to investigate relationships among social support, e-health literacy, and glycemic management behavioral decisions in pregnant women with gestational diabetes.MethodsUsing continuous sampling, an online cross-sectional survey was conducted among pregnant women with gestational diabetes who met the inclusion and exclusion criteria at four Class 3 hospitals in Fujian Province from October to December 2023. A structured questionnaire was used to collect data on general characteristics, socioeconomic status, social support, e-health literacy, and behavioral decision-making regarding glycemic management. Descriptive statistical analyses, correlation analyses, and mediation effects were used to assess associations.ResultsA total of 219 pregnant women with gestational diabetes participated, and 217 valid results were obtained. The level of glycemic management behavior decision-making in women with gestational diabetes was positively correlated with e-health literacy (r = 0.741, p < 0.01) and with perceived social support (r = 0.755, p < 0.01). E-health literacy was positively correlated with perceived social support (r = 0.694, p < 0.01). The indirect effect of perceived social support on glycemic management behavior decisions through e-health literacy (a*b) was 0.153, accounting for 38% of the total effect.ConclusionSocial support and e-health literacy in pregnant women with gestational diabetes are related to behavioral decision-making in glycemic management. The results of this study provide a reference for developing targeted measures to improve glycemic management behaviors in pregnant women with gestational diabetes, which is crucial for achieving sustainable glycemic management.